Stress resilience in Coffea arabica and Coffea canephora under harsh drought and/or heat conditions: selected genes, proteins, and lipid integrated responses - José C. Ramalho; José C. Ramalho; Isabel Marques; Isabel P. Pais; Isabel P. Pais; Jean Armengaud; Duarte Gouveia; Ana P. Rodrigues; Danielly Dubberstein; Danielly Dubberstein; Danielly Dubberstein; António E. Leitão; et al. (Frontiers in Plant Science)
Climate change has intensified the frequency, severity, and simultaneous incidence of drought and heat events, threatening the sustainability of agricultural systems worldwide. This implies the use of resilient plant genotypes able to activate defense mechanisms and overcome stress damage. We examined the leaf transcriptomic, proteomic, and membrane lipid responses in two cultivars of the main coffee-producing species—Coffea arabica L. cv. Icatu and Coffea canephora Pierre ex A. Froehner cv. Conilon Clone 153 (CL153—subjected to single and combined exposure to severe water deficit (SWD) and heat (up to 42°C/30°C, day/night). Well-watered (WW) plants maintained under adequate temperature (25°C/20°C) were gradually exposed to SWD and afterward to a slow temperature increase up to 42°C/30°C, followed by a 2-week recovery (Rec14) after reestablishing temperature and water conditions. Gene regulation and the respective protein contents were often marginally correlated; however, CL153 and, especially, Icatu showed markedly greater abundance of transcripts and/or proteins of most molecules to the imposed stress conditions, along with altered lipid profiles of chloroplast membranes. A set of key complementary response mechanisms, expressed either commonly or in a genotype- or stress-dependent manner, was identified. Additionally, the common responses to all stress conditions reflected stress crosstalk and interaction. Drought (with or without heat superimposition) constituted a greater response driver than heat in both genotypes. These showed de-novo synthesis of lipids and proteins, altering the fatty acid profile and unsaturation degree of chloroplast membranes and strengthening oxidative stress protection. The latter involved several genes and their respective proteins (e.g., aquaporins, PIPs and TIPs; chaperonins, Chape 20 and 60; dehydrin, DH1; dehydration-responsive element binding protein, DREB1D-F1; early light-induced protein, ELIP; heat shock protein 70 kDa, HSP70; ascorbate peroxidases, APXs; catalase, CAT), particularly prominent in Icatu. Also, a major recovery was found, although several genes/proteins exhibited lasting effects by Rec14. Overall, we revealed newly shared and specific (genotype or stress) responses of a complex network supporting Coffea spp. resilience. The identification of reliable stress-responsive traits is crucial to ensure the sustainability of this important tropical crop facing future climate stress scenarios, in which superimposed drought and heat stresses will be more frequent.